Content and delivery of pre-operative interventions for patients undergoing total knee replacement: a rapid review - Anna M. Anderson; Benjamin T. Drew; Deborah Antcliff; Anthony C. Redmond; Christine Comer; Toby O. Smith; Gretl A. McHugh (Systematic Reviews, 2022)
Abstract Background Total knee replacement (TKR) is a common operation typically performed for end-stage knee osteoarthritis. Patients awaiting TKR often have poor health-related quality of life. Approximately 20% of patients experience persistent pain post-TKR. Pre-operative TKR interventions could improve pre- and post-operative outcomes, but future research is required to inform their design. This review aimed to identify and synthesize recent literature on the content and delivery of pre-operative TKR interventions to help guide future research and clinical practice. Methods This rapid review included randomized trials of pre-operative TKR interventions (“outcomes studies”) and primary studies exploring patients’ and/or health professionals’ views of pre-operative TKR interventions (“views studies”). Medline, Embase, PsycINFO, CINAHL and the Cochrane Central Register of Controlled Trials were searched for English language studies published between January 2009 and December 2020. Eligible studies’ reference lists were screened. Studies were appraised using the Mixed Methods Appraisal Tool. The findings were narratively synthesized using a convergent segregated approach. Results From 3263 records identified, 52 studies were included (29 outcomes studies, 21 views studies, two outcomes/views studies). The studies’ methodological quality varied but was generally highest in qualitative studies. The outcomes studies investigated education (n=5), exercise (n=20), psychological (n=2), lifestyle (n=1), and/or other interventions (n=5). The views studies addressed education (n=20), exercise (n=3), psychological (n=1), lifestyle (n=4), and/or other interventions (n=1). Only three outcomes studies (two randomized controlled trials (RCTs) and a pilot study) compared the effectiveness of intervention components/delivery approaches. The two RCTs’ results suggest that pre-operative TKR exercise interventions are equally effective regardless of whether they include strength or strength plus balance training and whether they are hospital- or home-based. Personal tailoring and using more than one delivery format were associated with improved outcomes and/or perceived as beneficial for multiple intervention types. Conclusions Definitive evidence on the optimal design of pre-operative TKR interventions is lacking. Personal tailoring and employing multiple delivery formats appear to be valuable design elements. Preliminary evidence suggests that including balance training and hospital versus home delivery may not be critical design elements for pre-operative TKR exercise interventions. Systematic review registration PROSPERO CRD42019143248 Funder National Institute for Health and Care Research (ICA-CDRF-2018-04-ST2-006).